Ionization spectroscopy in cold rubidium atoms - Krzemień, Leszek; Baster, Kacper; Brzozowski, Krzysztof; Wojciechowski, Adam; Zachorowski, Jerzy; Gawlik, Wojciech (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
We demonstrate photoionization spectroscopy in cold rubidium atoms trapped in a working magneto-optical trap. Three-photon ionization with two-photon resonance proceeds along various channels, with the step-by-step 5S–5P–5D transition and with the two-photon excitation of the 5D or 7S state. The processes are monitored by measuring ion signals which allow sensitive spectroscopy of weak transitions in a cold-atom sample.
Optica Applicata, Vol. 40, 2010, nr 3, s. 571-576
Keywords: optyka; cold atoms; photoionization